Racial differences in the relationship between tobacco dependence and nicotine and carcinogen exposure - St Helen, Gideon (2012)
AIMS: To investigate the relationships between tobacco dependence, biomarkers of nicotine and carcinogen exposure, and biomarkers of nicotine and carcinogen exposure per cigarette in Black and White smokers. DESIGN AND PARTICIPANTS: 204 healthy Black (n=69) and White (n=135) smokers were enrolled in two clinical studies. MEASUREMENT: Nicotine equivalents (nicotine and its metabolites), 4-(methylnitrosamino)-1-(3)pyridyl-1-butanol (NNAL), and polycyclic aromatic hydrocarbon (PAH) metabolites were measured in urine. The Fagerström Test for Nicotine Dependence (FTND) and time to first cigarette (TFC) measured tobacco dependence. FINDINGS: Average TFC and FTND for Blacks and Whites were not significantly different. Urine NNAL and nicotine equivalents increased with increasing FTND in Whites but did not increase in Blacks (race x FTND interaction, both p<0.031). The interaction term was not significant for PAHs. An inverse relationship was seen between FTND and nicotine equivalents, NNAL, and PAH metabolites per cigarette in Blacks but remained flat in Whites (race x FTND interaction, all p≤0.039). Regardless of dependence (low dependence, TFC>15 minutes; high dependence, TFC≤15 minutes), FTND and TFC were not significantly correlated with urine nicotine equivalents and carcinogen exposure in Blacks. We found moderate correlations between FTND and TFC and nicotine equivalents and carcinogen exposure among Whites of low dependence and non-significant correlations among Whites of high dependence. CONCLUSION: In the US, tobacco dependence measures were linearly related to nicotine intake and carcinogen exposure in White but not in Black smokers. The relationship between dependence measures and tobacco biomarkers in Black smokers regardless of level of dependence resembled highly dependent White smokers.